Can Optic Flow Further Stimulate Treadmill-Elicited Stepping in Newborns? - Barbu-Roth, Marianne; Siekerman, Kim; Anderson, David I.; Donnelly, Alan; Huet, Viviane; Goffinet, François; Teulier, Caroline (Frontiers in Psychology, 2021)
Typically-developing three-day-old newborns take significantly more forward steps on a moving treadmill belt than on a static belt. The current experiment examined whether projecting optic flows that specified forward motion onto the moving treadmill surface (black dots moving on the white treadmill surface) would further enhance forward stepping. Twenty newborns were supported on a moving treadmill without optic flow (No OF), with optic flow matching the treadmill’s direction and speed (Congruent), with optic flow in the same direction but at a faster speed (Faster), and in a control condition with an incoherent optic flow moving at the same speed as in the Congruent condition but in random directions (Random). The results revealed no significant differences in the number or coordination of forward treadmill steps taken in each condition. However, the Faster condition generated significantly fewer leg pumping movements than the Random control condition. When highly aroused, newborns made significantly fewer single steps and significantly more parallel steps and pumping movements. We speculate the null findings may be a function of the high friction material that covered the treadmill surface.